Development of a Gamified Moodle Learning Management System for computer science education in Vocational High Schools - Tri Kurnia Maideshinta; Rini Novita; Rahayu Trisetyowati Untari (Researcher and Lecturer Society, 2025)
Digital transformation in education requires media that sustain student engagement in blended settings. This research seeks to design and develop a Moodle-based Learning Management System for Informatics at Vocational High School 1 Koto Baru and to verify its quality and usability for routine classroom use. The study uses a phased development approach (Analyse, Design, Develop, Implement, Evaluate). Participants were 44 tenth-grade learners and 2 instructors; quality was reviewed by 2 subject-matter experts and 3 media experts. Data came from structured questionnaires and were analysed descriptively in %. Findings show content quality is highly valid at 90% overall (89% content indicators, 92% instructional). Media quality is likewise highly valid at 91% (90% ease of use, 93% visual appeal). Classroom applicability is strong, with practicality of 92% for instructors and 92% for learners. Gamification mechanisms (points, levelling up, badges, and leaderboards) provide quick feedback, structured progress tracking, and support for learning orchestration. Overall, the product meets highly valid and practical criteria and is ready for adoption as a modular, trackable Moodle-based course for Informatics at the vocational high school level. Future work includes quasi-experimental tests of learning outcomes, replication across schools and subjects, performance evaluation under high access loads, and development of adaptive learning analytics.